31‐2: Measuring Interocular Geometric Distortion of Near‐Eye Displays. Issue 1 (29th May 2019) - Penczek, John; Hasan, Monirul; Denning, Bruce S.; Calpito, Robert; Austin, Richard L.; Boynton, Paul A.
Abstract : The evaluation of geometric distortion is presented for near‐eye displays with binocular vision. The true distortion with eye rotation is compared with pupil rotation using a reference goniometer for monocular vision. The left and right eye distortion data is then used to determine the distortion observed for binocular vision.